Porous polyacrylonitrile/graphene oxide nanofibers designed for high efficient adsorption of chromium ions (VI) in aqueous solution - Feng, Zhang-Qi; Yuan, Xu; Wang, Ting (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
•PAN/GO nanofibers with 5–200 nm pores were fabricated for efficient Cr(VI) removal.•BET specific surface area of the porous nanofibers was 164.2 ± 10.8 m2g−1.•Maximum experimental adsorption capacity of Cr(VI) was up to 382.5 ± 6.2 mg/g.•Reusability of the porous nanofibers was at least 20 times cycles.•Simple, low cost, green of one-step electrospinning had great industrial potential. Development of efficient adsorbent with low cost, simple and green production process, and zero secondary pollution for Cr(VI) removal in industrial applications is a great challenge for modern chemical and materials engineering. Here, we developed a new strategy for preparation of porous polyacrylonitrile (PAN)/graphene oxide (GO) nanofibers by simple one-step electrospinning of PAN/GO solution in N,N-dimethylformamide (DMF)/H2O mixed solvent. The resultant porous PAN/GO nanofibers possessed abundant nanopores (5–200 nm) and thus huge Brunauer-Emmett-Teller (BET) specific surface area (164.2 ± 10.8 m2g−1) and excellent interfacial compatibility. The porous structure maximized the adsorption function of the doped GO nanosheets for Cr(VI) ions, an unprecedented experimental Cr(VI) ions adsorption capacity of 382.5 ± 6.2 mg/g was achieved. And the porous PAN/GO nanofibers also exhibited excellent regeneration, after 20 times adsorption–desorption test, the desorption efficiency of the Cr(VI) ions stably maintained more than 75%. More importantly, compared to the current complex chemical synthesis and material structure design methods of Cr(VI) ions adsorbent, the simple one-step electrospinning fully showed great technical advantages for industrial applications including efficient (100% raw material utilization), green (no any harmful chemical by-products), low cost (only PAN and 1.98 wt% GO). Therefore, we suggested that the porous PAN/GO nanofibers will be a promising candidate in industrial applications as a solid adsorbent for Cr(VI) ions adsorption.